Transforming RN Roles in Community-Based Integrated Primary Care (TRIP): Background and Content. (3rd April 2019) - Humphrey Beebe, Lora; Mixer, Sandra J.; Thompson, Kathleen; Davis, Sharon; Elliott, Lizanne; Lakin, Brooke; Bullard, Tammy; Hurt, Maria; Niederhauser, Victoria
Abstract: Given the large body of evidence linking physical and mental health and the impetus provided by health care reform and the Affordable Care Act, the time is ripe to engage nurses in community based, integrated primary care teams to holistically address psychiatric, mental health and substance abuse needs. There is a compelling need for curricular redesign and clinical innovation to prepare an RN workforce for practice in community based integrated primary care teams. To that end, a faculty team of primary care, interprofessional education and content experts developed the Transforming RN Roles in Community Based Integrated Primary Care (TRIP) program for BSN students in a large university in the southeastern United States. The primary goals of the TRIP program are to build/implement an innovative BSN curriculum and expand our academic practice partnership by enhancing student clinical experiences with the goal of preparing an RN workforce for practice in community based integrated care teams. The TRIP program incorporates didactic, simulation and clinical components. Our first student cohort began the TRIP program in the fall of 2018 and will complete the program in spring 2020. In this paper, we provide details about the background, content and activities of this 4-semester (2 year) program.